2014
DOI: 10.1155/2014/406731
|View full text |Cite
|
Sign up to set email alerts
|

Topical Delivery of Aceclofenac: Challenges and Promises of Novel Drug Delivery Systems

Abstract: Osteoarthritis (OA), a common musculoskeletal disorder, is projected to affect about 60 million people of total world population by 2020. The associated pain and disability impair the quality of life and also pose economic burden to the patient. Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely prescribed in OA, while diclofenac is the most prescribed one. Oral NSAIDs are not very patient friendly, as they cause various gastrointestinal adverse effects like bleeding, ulceration, and perforation. To enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 75 publications
0
51
0
1
Order By: Relevance
“…13 Ethosomes, a type of carrier molecule, have many advantages for the treatment of eye irritation, including high stability; however, very few types are available for clinical application, and high concentrations can be toxic. 14,15 Cyclodextrin has been widely studied as a carrier in ophthalmic drug delivery systems and has been shown to prolong ocular retention time and increase drug solubility and bioavailability, thereby improving the drug's effectiveness. 11,16,17 Eye drops consisting of methazolamide in cyclodextrin can also reduce intraocular pressure, and are released over 6 h. The combination of acetazolamide, cyclodextrin, and triethanolamine was shown to increase permeation through the rabbit cornea by over ten-fold and to reduce intraocular pressure by .30%.…”
Section: Introductionmentioning
confidence: 99%
“…13 Ethosomes, a type of carrier molecule, have many advantages for the treatment of eye irritation, including high stability; however, very few types are available for clinical application, and high concentrations can be toxic. 14,15 Cyclodextrin has been widely studied as a carrier in ophthalmic drug delivery systems and has been shown to prolong ocular retention time and increase drug solubility and bioavailability, thereby improving the drug's effectiveness. 11,16,17 Eye drops consisting of methazolamide in cyclodextrin can also reduce intraocular pressure, and are released over 6 h. The combination of acetazolamide, cyclodextrin, and triethanolamine was shown to increase permeation through the rabbit cornea by over ten-fold and to reduce intraocular pressure by .30%.…”
Section: Introductionmentioning
confidence: 99%
“…[5] JOINS (SKI306X, SK Chemicals Co., Seongnam, Korea) is a mixture of extracts from Clematis mandshurica, Trichosanthes kirilowii, and Prunella vulgaris at a 1:2:1 weight ratio that has demonstrated efficacy for pain control in OA. [1] SKI306X has been widely used in combination with aceclofenac in Korea for pain control in OA.…”
Section: Transl Clin Pharmacolmentioning
confidence: 99%
“…Transport across the stratum corneum follows Fick's Law of diffusion, according to which the drug's flux depends on the drug oil/water partition coefficient, its concentration in the delivery system, thickness of the stratum corneum, and on the surface area of the exposed skin. Additional challenges that the dermal delivery system needs to overcome are local side effects (e.g., irritation, allergic reaction, and erythema), Nrf2-activating agent physiochemical properties such as low aqueous solubility and high log P, and chemical characteristics such as instability and photosensitivity [233]. The use of a topical delivery system in the case of activating the Keap1-Nrf2 pathway may present advantages such as avoidance from hepatic first-pass metabolism, accessibility to the skin site of action, prevention of naive cells from compound exposure and obviously patient compliance [233].…”
Section: Is the Usage Of Topical Delivery Systems Suitable?mentioning
confidence: 99%
“…Additional challenges that the dermal delivery system needs to overcome are local side effects (e.g., irritation, allergic reaction, and erythema), Nrf2-activating agent physiochemical properties such as low aqueous solubility and high log P, and chemical characteristics such as instability and photosensitivity [233]. The use of a topical delivery system in the case of activating the Keap1-Nrf2 pathway may present advantages such as avoidance from hepatic first-pass metabolism, accessibility to the skin site of action, prevention of naive cells from compound exposure and obviously patient compliance [233]. The avoidance of systemic circulation of the Nrf2-activating agent may be of specific importance since it was reported that Nrf2 activation may have unfavorable systemic metabolic effects.…”
Section: Is the Usage Of Topical Delivery Systems Suitable?mentioning
confidence: 99%